2016
DOI: 10.1002/jsfa.8025
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Cymbopogon citratus and Allium cepa essential oils increased antibacterial activity in leafy vegetables

Abstract: Leafy vegetables treated with the EO combination showed higher antibacterial protection and odor acceptability compared with individual EO treatments. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…A recent study showed that the application of Cymbopogon citratus and Allium cepa in combination to lettuce and spinach caused a greater reduction in pathogenic bacteria compared with higher doses of individual EOs. Also, no significant differences were found among odor acceptability of control vegetables and those treated with the EO combination (Ortega‐Ramirez et al, ). Moreover, encapsulated garlic oil applied in fresh‐cut tomatoes reduces microbial growth without affecting sensorial acceptability (Ayala‐Zavala & González‐Aguilar, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the application of Cymbopogon citratus and Allium cepa in combination to lettuce and spinach caused a greater reduction in pathogenic bacteria compared with higher doses of individual EOs. Also, no significant differences were found among odor acceptability of control vegetables and those treated with the EO combination (Ortega‐Ramirez et al, ). Moreover, encapsulated garlic oil applied in fresh‐cut tomatoes reduces microbial growth without affecting sensorial acceptability (Ayala‐Zavala & González‐Aguilar, ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of oregano and rosemary EOs combination against pathogens was studied by determining the fractional inhibitory concentration index (FICI) using the checkerboard microdilution method (Ortega‐Ramirez et al, ). Serial dilutions of individual EO were prepared in MH broth and combined together.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Ortega-Ramirez et al [10] reported the inhibitory effect of C. citratus EO against planktonic E. coli at 2.21 mg/mL. On the other hand, other EOs also showed efficacy to inhibit E. coli O157:H7; for example, Kim et al [19] reported that concentrations of 0.001 to 0.01mg/mL of bay, clove, and pimento berry EO significantly inhibited the biofilm formation of E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, citral and geraniol also showed antibacterial activity against E. coli as well as anti-quorum sensing activity at concentrations of 0.01 and 0.06 mg/mL, respectively [9]. On the other hand, C. citratus EO in combination with Allium cepa EO reduced the presence of E. coli in lettuce and spinach [10]. However, its antibacterial activity on planktonic cells could differ from the expected response against biofilms.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, SC seeds generated from the ayurvedic industry are chosen for the current study as it undergoes minimum thermal processing during the preparation of formulations and thereby retains bio‐actives after processing. EOs are known to have antimicrobial properties, since ancient years (Ortega‐Ramirez et al, ; Yang, Chao, & Liu, ). Cumin EO is reported to exhibit potential antioxidant and antimicrobial properties (Chen et al, ; Nisha, Husain, & Ali, ).…”
Section: Introductionmentioning
confidence: 99%